Effect of acute kidney injury and overall survival in patients with postoperative head and neck cancer who received chemoradiotherapy with cisplatin: A supplementary analysis of the phase II/III trial of JCOG1008 - Yoshinori Imamura; Naomi Kiyota; Makoto Tahara; Takeshi Kodaira; Ryuichi Hayashi; Hiroshi Nishino; Yukinori Asada; Hiroki Mitani; Shigemichi Iwae; Naoki Nishio; Yusuke Onozawa; Nobuhiro Hanai; et al. (Cancer Medicine)
Abstract Background In a randomized phase II/III trial (JCOG1008), weekly cisplatin (40 mg/m2) was non‐inferior to 3‐weekly cisplatin (100 mg/m2) for postoperative high‐risk head and neck cancer. We investigated how acute kidney injury (AKI), a major dose‐limiting toxicity effect of cisplatin, affects overall survival (OS). Methods We analyzed 251 patients from JCOG1008 receiving chemoradiotherapy. AKI was defined based on AKI Network criteria (serum creatinine increase of ≥0.3 mg/dL or ≥1.5‐fold [≥ stage I]) within 30 days after completing chemoradiotherapy. OS in the two arms was compared according to AKI development using the log‐rank test. Results The total incidence of AKI was lower in the weekly arm than in the 3‐weekly arm (38/122 [31.1%] vs. 56/129 [43.4%]). Additionally, stage II/III AKI occurred less frequently in the weekly arm than in the 3‐weekly arm (8/122 [6.6%] vs. 19/129 [14.7%]). Cisplatin doses were similar in the weekly arm for patients with and without AKI (median, 238.6 mg/m2 vs. 239.2 mg/m2; p = 0.94), but lower in the 3‐weekly arm for those who developed AKI (median, 276.3 mg/m2 vs. 297.4 mg/m2; p = 0.007). In the weekly arm, there was no difference in OS between patients with and without AKI (hazard ratio [HR], 1.06; 95% confidence interval [CI], 0.53 to 2.10). However, in the 3‐weekly arm, patients with AKI had poorer OS than those without AKI (HR, 1.83; 95% CI, 1.04 to 3.21). Conclusions In this supplementary analysis of JCOG1008 data, AKI impacted the OS of patients with head and neck cancer undergoing postoperative chemoradiotherapy in the 3‐weekly arm but not in the weekly arm. Our results further endorse the utilization of weekly cisplatin at 40 mg/m2 in this setting.